Structure of Nascent ϕX174 Replicative Form: Evidence for Discontinuous DNA Replication - Eisenberg, Shlomo (1974)
ϕX174 RF (replicative form) II DNA, labeled in vivo with [methyl-(3)H]thymidine, was isolated from Escherichia coli polA (DNA polymerase I-deficient) and polA(+) cells during RF replication. [(32)P]dCMP was incorporated into the gaps present in the RF II DNA with [α-(32)P]dCTP and T4 DNA polymerase. Sedimentation in alkaline sucrose gradients revealed that much of the incorporated (32)P was present in a heterogeneous collection of fragments shorter than unit length. Inclusion of polynucleotide ligase in the gap-filling reaction increased the average size of the (32)P-labeled fragments. Gel electrophoresis of the products formed by digestion of the (32)P-labeled RF II molecules with the restriction nuclease, endonuclease R, indicated that in the population of RF II molecules gaps could occur anywhere in the genome. Competition-annealing experiments provided evidence that the majority of the label incorporated into gaps was present in the minus strand. RF II molecules isolated from polA(+) cells were enriched for gaps in a unique region of the genome in comparison with RF II molecules isolated from polA cells. The presence of multiple gaps in the minus strand implies that it is synthesized by a discontinuous mechanism during ϕX RF replication.